Les juristes et l’histoire. Pour une nouvelle archéologie du droit - Aldo Schiavone (Clio@Themis)
This article questions the crisis of the statutory law in a global world, and the formation of a new paradigm of “legal”. In this context, it considers the tasks and the perspectives today’s legal historians have to embrace.